1996
DOI: 10.1002/(sici)1098-2361(1996)15:5<455::aid-zoo3>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Allometry and ecology of feeding behavior and digestive capacity in herbivores: A review

Abstract: The purpose of this review is to give some perspective of the factors that influence feeding behaviors and the ability of herbivores to adapt to diets. The most important of these are digestibility, ability to select feed, and achievement of a nutritionally adequate intake. Plant morphology, observed feeding behavior, body size, and gut architecture and size impinge upon these factors. Feeding behavior and dietary specializations are associated with adaptations of gut and mouth parts as well as body size. Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 68 publications
7
154
0
4
Order By: Relevance
“…The higher OMD CPf measured at pasture has usually been related to the ability of grazing animals to select betterquality forage (Minson, 1990;Van Soest, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher OMD CPf measured at pasture has usually been related to the ability of grazing animals to select betterquality forage (Minson, 1990;Van Soest, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, the fundamentals of animal feeding at pasture are often based on the extrapolation of results obtained indoors, although some differences may exist between these two ways of feeding. Hence, although a positive correlation between intake and digestibility has been reported indoors (Minson, 1990;Ketelaars and Tolkamp, 1992;Archimede et al, 2000), other studies have reported the opposite at pasture (Hitchcock et al, 1990;Van Soest, 1996;Boval et al, 2007). However, these results were produced in studies carried out with different forage species, under different climatic and management conditions.…”
Section: Introductionmentioning
confidence: 93%
“…Many methods are available but that most widely used is in vitro digestibility (Kitessa et al, 1999) even though values often have to be adjusted to estimate in vivo digestibility. Also, although in Grassland, management and methodological progress tropical pastures some studies (Minson, 1990;Archimede et al, 2000) have reported good relationships, in many others there was often a poor relationship between digestibility and voluntary intake or LW gain (VanSoest, 1996;Boval et al, 2007b).…”
Section: Evaluation Of Pasture Attributesmentioning
confidence: 99%
“…for small (rodent) herbivores (Justice and Smith 1992;Smith 1995), to include effects of differences in relative intake and food sorting; Owen-Smith (1988) and Van Soest (1996) also emphasized that larger ungulates can support their lower specific metabolic requirements either by accepting forage of lower quality, or by ingesting lesser amounts of regular quality forage per day, or some combination of both. Thus, larger animals should eat diets of lower nutritional quality than those selected by smaller herbivores, but the difference should be less marked than predicted simply on the basis of the body size-metabolic rate relationship.…”
Section: Ecophysiological Theories On the Digestive Relevance Of Bodymentioning
confidence: 99%
“…Case 1979;Owen-Smith 1988;Van Wieren 1996;Brashares et al 2000;Gagnon and Chew 2000). This is not due to physiological limitations but to forage abundance (Van Soest 1996). Large species cannot be as selective as small species, and the large amounts of forage necessary to supply large species are available mainly as grasses.…”
Section: Open Questions In Large Herbivore Digestive Physiologymentioning
confidence: 99%